Training Teaching at the Right Level (TaRL) and Culturally Responsive Teaching (CRT) [Pelatihan Pembelajaran Berbasis Level Berpikir serta Berlatar Belakang Budaya] - Wiwi Siswaningsih; Asep Kadarohman; Triannisa Rahmawati; Nahadi Nahadi; Florentina Maria Titin Supriyanti; Zackiyah Zackiyah; Sjaeful Anwar (Universitas Pendidikan Indonesia (UPI), 2023)
Kegiatan Pengabdian pada Masyarakat (PkM) dilaksanakan dengan memberikan pelatihan pada guru di Kabupaten Sukabumi. Kegiatan ini bertujuan untuk memberikan wawasan mengenai pengembangan keprofesionalan guru, lebih khusus seberapa dalam penerapan Teaching at the Right Level (TaRL) dan Culturally Responsive Teaching (CRT) dalam kegiatan pembelajaran di sekolah, juga bagaimana guru dapat menuliskan data kegiatan pembelajaran di sekolah menjadi suatu bentuk artikel. Kegiatan dilaksanakan dengan terstruktur dan sistematis dengan total waktu kegiatan setara 32 Jam Pelajaran (JP) secara daring dan luring. Hasil dari pengabdian ini diketahui bahwa guru mendapat banyak pengetahuan strategi menghubungkan pembelajaran kimia berlatar belakang budaya dan mengacu pada tingkat kemampuan siswa. Selain itu, lebih dari 65% siswa menyukai kegiatan pembelajaran kimia dengan pendekatan budaya lokal, dan hampir 100% siswa merasa puas dengan pembelajaran yang dilakukan oleh guru, yang didasarkan pada tingkat pengetahuan siswa, serta guru berhasil mendiseminasikan tiga tulisan pada topik pemahaman konsep dan pengetahuan prasyarat kimia, profil kemampuan berpikir logis siswa dengan pendekatan TaRL, dan pemahaman siswa SMA kelas X pada materi ikatan kimia dengan menggunakan model guided discovery learning.Community Service activities are carried out by providing training to teachers in Sukabumi Regency. This activity aims to provide insight into teacher professional development, more specifically how deeply Teaching at the Right Level (TaRL) and Culturally Responsive Teaching (CRT) are implemented in learning activities at school, as well as how teachers can write data on learning activities at school into article form. Activities were carried out in a structured and systematic manner with a total activity time equivalent to 32 JP online and offline. As a result of this service, it is known that teachers gain a lot of knowledge about strategies relating to chemistry learning with cultural backgrounds and referring to students' ability levels. Apart from that, more than 65% of students liked chemistry learning activities with a local cultural approach, and almost 100% of students were satisfied with the learning carried out by the teacher, which was based on the student's level of knowledge, and the teacher succeeded in disseminating three articles on understanding chemistry concepts and prerequisite knowledge; profile of students' logical thinking abilities using the TaRL approach, and class X high school students' understanding of chemical bonding material using the guided discovery learning model.